2015
DOI: 10.1093/infdis/jiv098
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into the Protective Role of Hemoglobin S and C AgainstPlasmodium falciparumParasitemia

Abstract: Although hemoglobin S (HbS) and hemoglobin C (HbC) are well known to protect against severe Plasmodium falciparum malaria, conclusive evidence on their role against infection has not yet been obtained. Here we show, in 2 populations from Burkina Faso (2007–2008), that HbS is associated with a 70% reduction of harboring P. falciparum parasitemia at the heterozygous state (odds ratio [OR] for AS vs AA, 0.27; 95% confidence interval [CI], .11–.66; P = .004). There is no evidence of protection for HbC in the heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
1
24
2
Order By: Relevance
“…Studies in murine models have demonstrated that the accelerated breakdown of haem by the increased induction of HO-1 prevents the onset of experimental cerebral malaria in mice [16,17]. Contrary to reports that have implicated the reduction of parasitaemia as a cause of the reduced susceptibility to severe complications of malaria in patients with the HbAS genotype [3,12,32], we found no significant difference in parasite densities between patients with the HbAS genotype and patients with the HbAA genotype during acute malaria infection. Our cohort of children does not have severe forms of malaria; therefore, we cannot rule out the possibility of a difference in parasitaemia between the genotypical groups if they have severe malaria.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in murine models have demonstrated that the accelerated breakdown of haem by the increased induction of HO-1 prevents the onset of experimental cerebral malaria in mice [16,17]. Contrary to reports that have implicated the reduction of parasitaemia as a cause of the reduced susceptibility to severe complications of malaria in patients with the HbAS genotype [3,12,32], we found no significant difference in parasite densities between patients with the HbAS genotype and patients with the HbAA genotype during acute malaria infection. Our cohort of children does not have severe forms of malaria; therefore, we cannot rule out the possibility of a difference in parasitaemia between the genotypical groups if they have severe malaria.…”
Section: Discussioncontrasting
confidence: 99%
“…While protective associations between certain RBC variants and severe malaria have been shown consistently [7,18], associations with uncomplicated malaria have been less straightforward. Multiple studies showed reduced risk of malaria [19][20][21][22][23][24] and lower parasite densities [4,25,26] with HbAS compared to wild-type. For alpha thalassaemia, studies suggested both protection against and enhancement of malaria [5,6,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed evidence related to the role of hemoglobin S and C in the protection against severe and uncomplicated malaria [21,22]. The role of hemoglobin S and C has already shown in the protection against malaria infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…The study site has been already described elsewhere [12]. Plasma samples were obtained from children and adults belonging to 3 sympatric ethnic groups (Mossi, Fulani, and Rimaïbé).…”
Section: Study Site and Samples Collectionmentioning
confidence: 99%
See 1 more Smart Citation